Dorota Żołądź-Strzelczyk, (2022). Pustelnik z Pałacu Ordynackiego. Dole i niedole Marcina Nikuty, Wrocław: Wydawnictwo Chronicon, ss. 68 - Kabacińska-Łuczak, Katarzyna (Studia Edukacyjne, 2023)
Recenzja: Dorota Żołądź-Strzelczyk Pustelnik z Pałacu Ordynackiego. Dole i niedole Marcina Nikuty Wydawnictwo Chronicon, ss. 68, 2022